2021
DOI: 10.1097/scs.0000000000008150
|View full text |Cite
|
Sign up to set email alerts
|

Precision Pharyngeal Flap: An Individualized, Patient-Specific Surgery for the Treatment of Velopharyngeal Insufficiency

Abstract: Background:The pharyngeal flap is one of the most common secondary surgeries for the correction of velopharyngeal insufficiency (VPI) for patients with cleft palate and/or cleft lip and palate. This study aimed to demonstrate the effectiveness of the precision pharyngeal flap surgery performed by the senior author. Materials and Methods: Children with VPI, who underwent precision pharyngeal flap, were retrospectively examined. All surgical procedures were performed by the senior author. The flap size was indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The success rate of 92% is comparable to other studies that place the success rate of pharyngeal flap surgery in the range of 81.5%–97%. 5 The data of this study expand upon previous research through the addition of a surgeon and a wider variation in technique. A single-surgeon study by Baek et al demonstrated that preoperative planning using FVNP resulted in velopharyngeal competency in 96% of patients.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The success rate of 92% is comparable to other studies that place the success rate of pharyngeal flap surgery in the range of 81.5%–97%. 5 The data of this study expand upon previous research through the addition of a surgeon and a wider variation in technique. A single-surgeon study by Baek et al demonstrated that preoperative planning using FVNP resulted in velopharyngeal competency in 96% of patients.…”
Section: Discussionsupporting
confidence: 66%
“…The success rate of 92% is comparable to other studies that place the success rate of pharyngeal flap surgery in the range of 81.5%-97%. 5 The data of this study expand upon previous research through the addition of a surgeon and 5 Our study encompassed a larger number of surgeons and surgical techniques but produced comparable outcomes due to preoperative planning and anatomic information using MPVF and FVNP. All 35 cases of VCFS underwent a neck CT scan with contrast before T&A, followed by pharyngeal flap creation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations